Effect of a mindfulness program on stress, anxiety, depression, sleep quality, social support, and life satisfaction: a quasi-experimental study in college students - Alvarado-García, Paul Alan Arkin; Soto-Vásquez, Marilú Roxana; Infantes Gomez, Francisco Mercedes; Guzman Rodriguez, Natalia Mavila; Castro-Paniagua, William Gil (Frontiers in Psychology, 2025)
IntroductionThe university experience often brings various personal and academic challenges that can negatively impact students’ mental health. This research aimed to evaluate the effect of a mindfulness program on stress, anxiety, depression, sleep quality, social support, and life satisfaction among university students.MethodsA quasi-experimental study was conducted with 128 participants, divided into experimental and waiting list control groups. The experimental group participated in a mindfulness meditation program consisting of 12 weekly sessions. Pre-test and post-test measurements were performed using the Perceived Stress Scale (PSS-10), the Zung Self-Rating Anxiety Scale (SAS), the Zung Self-Rating Depression Scale (SDS), the Pittsburgh Sleep Quality Index (PSQI), the Medical Outcomes Study Social Support Survey (MOS-SS), and the Satisfaction with Life Scale (SWLS) to assess the variables.ResultsThe experimental group showed statistically significant differences between the study phases and the groups after the intervention for all the variables examined (p < 0.05). The effect sizes calculated using the HC3 model were stress (η2 = 0.376), anxiety (η2 = 0.538), depression (η2 = 0.091), sleep quality (η2 = 0.306), social support (η2 = 0.704), and life satisfaction (η2 = 0.510). The mindfulness program was shown to be effective in reducing levels of stress, anxiety, and depression while also improving sleep quality, social support, and life satisfaction in college students.ConclusionThese findings indicate that mindfulness meditation may be valuable for enhancing psychological well-being in educational settings.